2006
DOI: 10.1348/135532505x68719
|View full text |Cite
|
Sign up to set email alerts
|

The relative validity of psychopathy versus risk/needs‐based assessments in the prediction of adolescent offending behaviour

Abstract: Purpose. The predictive validity of the psychopathy checklist‐youth version (PCL:YV) and Youth Level of Service/Case Management Inventory (YLS/CMI) for juvenile offenders were compared to examine whether a broad needs–risk tool predicted violence better than a focused individual assessment of psychopathy. Methods. 94 adolescents from residential and secure units were interviewed and assessed using the PCL:YV and YLS/CMI. Total scores were retrospectively applied to staff‐recorded incidents of violence, total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 41 publications
5
36
0
1
Order By: Relevance
“…Studies included different recidivism outcomes such as general recidivism, violent recidivism, and non-violent recidivism, among others. There was one study (Marshall, Egan, English, & Jones, 2006) that used the YLS/CMI to predict the risk for offending against staff while incarcerating. Since the dependent variable was offending while incarcerated rather than recidivism once released, this study was not included.…”
Section: Methods For Locating Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies included different recidivism outcomes such as general recidivism, violent recidivism, and non-violent recidivism, among others. There was one study (Marshall, Egan, English, & Jones, 2006) that used the YLS/CMI to predict the risk for offending against staff while incarcerating. Since the dependent variable was offending while incarcerated rather than recidivism once released, this study was not included.…”
Section: Methods For Locating Studiesmentioning
confidence: 99%
“…While Olver, Stockdale and Wong (2012) found that the instrument worked equally well on some outcomes, they found that it predicted male recidivism better for others. While the study completed by Marshall, Egan, English, and Jones (2006) looked at violent offending against correctional staff rather than recidivism, it revealed that the YLS/CMI was better at predicting male violence than female violence.…”
Section: Yls/cmi -Previous Findingsmentioning
confidence: 99%
“…We included incarcerated subjects because we had difficulty recruiting the desired number of probationers. In addition, the YLS/ CMI is used in other jurisdictions in facilities (see, for example, Marshall et al, 2006), thus the tool can apply to these youth. Staff at the facility and community supervising the youth were informed of the subject's names and asked to obtain informed consent from guardians and then gauge the youth's interest in taking part in the study.…”
Section: Yls/cmimentioning
confidence: 99%
“…An important question is whether the construct of psychopathy is associated with similar outcomes in youth as has been found in samples of incarcerated adults (e.g., persistent and chronic violent offending; Harris, Rice, & Cormier, 1991;Salekin, Rogers, & Sewell, 1996). To date, the literature linking psychopathic features to concurrent and future violence among male juveniles has been largely consistent with the adult offender literature (Corrado, Vincent, Hart, & Cohen, 2004;Kosson et al, 2002;Marshall, Egan, English, & Jones, 2006). As interest in youth psychopathy has grown, researchers have begun to construct various self-report measures that represent key features of psychopathy as exemplified in the Psychopathy Checklist, Youth Version (PCL:YV; Forth et al, 2003).…”
Section: Juvenile Psychopathymentioning
confidence: 90%